Training-load management ambiguities and weak logic: creating potential consequences in sport training and performance - West, S.; Shrier, I.; Impellizzeri, F. M.; Clubb, J.; Ward, P.; Bullock, G. (International Journal of Sports Physiology and Performance, 2025)
Background: The optimization of athlete training load is not a new concept; however in recent years, the concept of "load management" is one of the most widely studied and divisive topics in sports science and medicine.